Coexistence of large out-of-plane and in-plane piezoelectricity in 2D monolayer Li-based ternary chalcogenides LiMX2 - Liu, Siyuan; Chen, Weizhen; Liu, Chang; Wang, Bing; Yin, Huabing (Results in physics, 2021)
•The out-of-plane and in-plane piezoelectricity in 2D Li-based ternary chalcogenides LiMX2 are investigated.•We propose a simple correlation between in-plane piezoelectricity and atomic polarizability.•The out-of-plane piezoelectric coefficients d31 of LiMX2 monolayers are larger than those of most reported 2D materials. Two-dimensional (2D) piezoelectric materials that can achieve conversion between mechanical and electrical energy are of notable interest for functional materials. However, most 2D materials have only in-plane piezoelectricity, which limits their applications in vertically integrated nanoelectromechanical systems. Here, we employ first-principles calculations to predict properties of a family of piezoelectric materials—Li-based ternary chalcogenides LiMX2 (M = Al, Ga, and In; X = S, Se, and Te). These materials exhibit the coexistence of intrinsic out-of-plane and in-plane piezoelectricity with coefficients d11 = 1.48–8.66 pm/V and d31 = 0.24–0.83 pm/V, respectively. The out-of-plane piezoelectric coefficients d31 of LiAlSe2, LiGaTe2, and LiAlTe2 in particular are as high as 0.61, 0.70, and 0.83 pm/V, respectively, much larger than those of most reported 2D materials. This enhancement can be attributed to the unique double-buckled stacking structure of these LiMX2 monolayers. It is also found that the in-plane piezoelectricity is highly dependent on the ratio of anion and cation polarizabilities, whereas the out-of-plane piezoelectricity exhibits a complicated variation trend with respect to the order of atomic number. The coexistence of large out-of-plane and in-plane piezoelectricity endows LiMX2 monolayers with potential applications in both directional and nondirectional piezoelectric devices.